On the fracture response of shape memory alloys by void growth and coalescence. (February 2021) - Makkar, J.; Baxevanis, T.
Abstract: Although Shape Memory Alloys (SMAs) belong to a relatively brittle class of materials, that of intermetallics, their fracture surfaces are characterized by both cleavage and dimples, with the latter being indicative of ductile rupture. Two clear differentiators of SMAs from other intermetallics, which may contribute to the presence of ductile rupture are their ability to transform their crystallographic structure and the presence of precipitates in large volume fractions. In this paper, unit cell simulations are employed in an effort to quantify the relative importance of the two fracture mechanisms in the overall failure response of these materials. The numerical simulations involve a single pre-existing void, assumed to have initiated from a second phase particle, embedded in a SMA matrix material. Thus, the unit cell studies allow for an investigation of void growth and coalescence, ignoring void formation and its footprint in the subsequent microstructure evolution. The numerical studies show that void growth is rather limited before the peak stress-value in the effective stress–effective strain response of the unit cell for initial void-volume fractions representative of precipitation-hardened SMAs. Given the available experimental observations on notched round bars, which indicate that precipitation-hardened SMAs fail in a stress-controlled manner, the numerical studies suggest that void growth and coalescence should play a minor role in the formation of dimples, as compared to that of void nucleation and cleavage, and in turn into the fracture response of precipitated SMAs. Highlights: Unit cell simulations are employed to investigate void growth and coalescence in SMAs. Void coalescence is limited in SMAs that fail in a stress-controlled manner. Void growth is restricted by the high-volume fractions of precipitates and cleavage. Void initiation and cleavage should dominate the fracture response of SMAs.